An Experimental Investigation for Comparison of Porous Concrete and Conventional Concrete in Strength (International Journal of Innovative Research in Computer Science & Technology, 2022)
Previous and current concrete is defined as  concrete that contains little to no fine aggregate, coarse  aggregate, or cement particles. It is considered "green  binding" and is used in structural applications. Pervious  concrete is also known as no-fine aggregate. Compared to  ordinary concrete, it uses fewer raw materials. When utilised  in pavement applications, pervious concrete aids in  groundwater recharging, water direct drainage, and also has  greater insulating qualities when used in walls. Current or  previous building uses concrete that has been specially  formulated to have a higher water permeability, allowing  water to move through the structure's interconnected huge  pores. The findings of an investigation into the production of  pervious concrete using low cement concentration and coarse  aggregate are reported in this work.
Keywords: Pervious Concrete; Super Plasticizer Sp430; Void Ratio; Mix Design